Asuhan Pada Ibu Hamil Bersalin Dengan Laserasi Derajat II, Nifas, Bayi Baru Lahir Pada NY. “S” G1P0A0 Di Puskesmas Pamandegan Kabupaten Lebak Tahun 2024 - Aridawarni, Yulica; Hildah (Prodi DIII Kebidanan La Tansa Mashiro, 2024)
Every woman will go through the process of pregnancy, childbirth, postpartum and family planning, these are physiological processes. During the process, there is a possibility of health problems that can increase morbidity and even death in mothers and babies. In Lebak Regency in 2022, there were 42 cases of maternal mortality and 301 cases of maternal mortality. Therefore, a solution is needed to prevent or overcome these problems, one of which is continuous care (Continuity of Care). The purpose of this study is to provide comprehensive care from pregnancy to family planning, Writing a Comprehensive Case Study Report using Varney's 7-step midwifery management approach and documented in SOAP form. The results of this study obtained a diagnosis of Mrs. S, 21 years old, G1P0A0, 39 weeks of pregnancy, in the first stage the cervical dilation did not cross the alert line, lasted 15 hours and the second stage lasted 16 minutes. The baby was born spontaneously, cried immediately, moved actively, and had reddish skin color. The third stage lasted 10 minutes with active management of the third stage, the placenta was born spontaneously and completely, bleeding ±150 cc. In the fourth stage, there was grade II laceration. Furthermore, monitoring for 2 hours postpartum, bleeding ±65 cc and uterine contractions were good. The results of the study can be concluded that the implementation and provision of comprehensive midwifery care for pregnant women, mothers in labor, postpartum and newborns in Mrs. S is expected to be able to apply the IEC that has been given during the care so that the condition of the mother and baby does not experience complications.